The Impact of Visual Thinking Approach to Promote Elementary Students’ Problem Solving Skill in Mathemathics - Muhammad Fendrik; Elvina Elvina (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This study aims to examine the influence of visual thinking learning to problemsolving skill. Quasi experiments with the design of this non-equivalent controlgroup involved Grade V students in one of the Elementary Schools. The design ofthis study was quasi experimental nonequivalent control group, the researchbullet used the existing class. The results of research are: 1) improvement ofproblem soving skill. The learning did not differ significantly between studentswho received conventional learning. 2) there is no interaction between learning(visual thinking and traditional) with students' mathematical skill (upper, middleand lower) on the improvement of skill. 3) there is a difference in the skill oflanguage learning that is being constructed with visual learning of thought interms of student skill (top, middle and bottom).